Editorial - Miramontes, Pedro (INTER DISCIPLINA, 2020)
Criticality refers to the study of those systems of Nature, whether biological, physical or social that are close to a critical point. This, in turn, is a state in which systems have unique properties: their correlation function diverges, which means that the system is fully integrated; what happens in one of its parts affects the rest. At equilibrium points the values of some of the variables that characterize the system exhibit a distribution of power law. That is, there are few very large values, a regular number of regular values and many small values. Within the infinity of association rules that can follow this verbal description, those whose graph is a straight line that descends when logarithmic coordinates are used are laws of power.